2023
DOI: 10.1007/s00170-023-12354-5
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of microstructure and tribological property of Ti-6Al-4V alloy by laser shock peening processing

Cheng Gu,
Zenghui Tian,
Jianhua Zhao
et al.

Abstract: Laser shock peening (LSP) is a process to introduce compressive residual stresses for improved surface properties of materials. In this study, the effect of LSP on the microstructure and tribological property of Ti-6Al-4V alloy was investigated. The surface and cross-sectional microstructure of the samples show that the shape of the β phase changes from a long strip to a short bar and granular after the LSP treatment. With the increase of laser energy, the surface roughness decreases gradually while the surfac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Laser shock peening (LSP) is an advanced surface treatment technique based on laser shock-induced plastic deformation without a thermal effect. These shockwaves induce changes in the material microstructure and residual stress distribution, resulting in improved surface hardening, wear resistance, and tribological performance [79,80]. Shukla et al [81] demonstrated increased net compressive stresses from 104 MPa to 168 MPa using LSP on Al 2 O 3 ceramics.…”
Section: Laser Ablation and Texturingmentioning
confidence: 99%
“…Laser shock peening (LSP) is an advanced surface treatment technique based on laser shock-induced plastic deformation without a thermal effect. These shockwaves induce changes in the material microstructure and residual stress distribution, resulting in improved surface hardening, wear resistance, and tribological performance [79,80]. Shukla et al [81] demonstrated increased net compressive stresses from 104 MPa to 168 MPa using LSP on Al 2 O 3 ceramics.…”
Section: Laser Ablation and Texturingmentioning
confidence: 99%